The big book of natural wonders - Bramwell, Martyn (Hamlyn young books, London, 1992)
Children are facinated by the wonders of nature and this book describes some of the most interesting and exciting natural phenomena around the world. There are sections on volcanoes, earthquakes, the tallest mountains and the deepest parts of the oceans.